Mining Double-line Spectroscopic Candidates in the LAMOST Medium-resolution Spectroscopic Survey Using a Human–AI Hybrid Method - Shan-shan Li; Chun-qian Li; Chang-hua Li; Dong-wei Fan; Yun-fei Xu; Lin-ying Mi; Chen-zhou Cui; Jian-rong Shi (The Astrophysical Journal Supplement Series, 2024)
We utilize a hybrid approach that integrates the traditional cross-correlation function (CCF) and machine learning to detect spectroscopic multiple star systems, specifically focusing on double-line spectroscopic binaries (SB2s). Based on the ninth data release (DR9) of the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST), which includes a medium-resolution survey (MRS) containing 29,920,588 spectra, we identify 27,164 double-line and 3124 triple-line spectra, corresponding to 7096 SB2 candidates and 1903 triple-line spectroscopic binary (SB3) candidates, respectively, representing about 1% of the selected data set from LAMOST-MRS DR9. Notably, 70.1% of the SB2 candidates and 89.6% of the SB3 candidates are newly identified. Compared to using only the traditional CCF technique, our method significantly improves the efficiency of detecting SB2s, saving time on visual inspections by a factor of 4.